THE RELIABILITY OF THE ENGLISH SUMMATIVE TEST FOR THE SECOND GRADE STUDENTS OF SENIOR HIGH SCHOOL - Abdul Muhid Murtadho (Journal of English Language and Literature (JELL), 2017)
This research was held to check out the reliability of the English Summative test for the second grade students of the Senior High School. This Research was held at SMA 3 Tambun Selatan – Bekasi. The writer took 43 students as sample for research. The research instrument is The English Summative test of second semester for second grade students. The English Summative test is tested twice. The methodolgy used by the writer is Test – Retest and after that the writer count the correlation of those tests using formula of Pearson Product Moment. From The research writer found that the English Summative test for the second semester of second grade students in SMA 3 Tambun Selatan Bekasi period 2009 / 2010 is reliable